Supramolecular ionic liquids, solid electrolyte membranes, solid-state lithium metal batteries and devices

By using supramolecular liquids and polymer matrix with benzophenylagen structure, solid electrolyte membranes with high ionic conductivity are prepared, which solves the problem of low conductivity of existing solid electrolyte materials and improves the energy density of lithium metal batteries and security.

CN115053378BActive Publication Date: 2025-02-18CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202080095432.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-07-30
Publication Date
2025-02-18
Estimated Expiration
2040-07-30

AI Technical Summary

Technical Problem

The existing solid electrolyte materials have low ionic conductivity, which limits the energy density and safety of lithium metal batteries.

Method used

A supramolecular ionic liquid with a benzophenylagen structure is used to form a columnar structure through π-π stacking to improve ionic conductivity, and a high-performance solid electrolyte membrane is prepared by combining polymer matrix and lithium salt.

Benefits of technology

It significantly improves the ionic conductivity of the solid electrolyte membrane at room temperature, approaches the level of liquid electrolyte, enhances the energy density and cycling performance of lithium metal batteries, and improves the safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115053378B_ABST
    Figure CN115053378B_ABST
Patent Text Reader

Abstract

A supramolecular ionic liquid, a solid electrolyte membrane, a solid lithium metal battery (5) and a device. The supramolecular ionic liquid provided has a triphenylene structure as shown in formula (I), wherein R1 is selected from an ether group, a polyether group, a halogenated ether group or a halogenated polyether group having 1 to 16 carbon atoms; and R2 is selected from an ether group or a polyether group having 1 to 16 carbon atoms. The ionic conductivity of the supramolecular ionic liquid provided at room temperature is as high as 10 ‑3 S / cm, and the ionic conductivity of its super-prepared solid electrolyte membrane is also 10 ‑3 S / cm or above, close to the level of liquid electrolytes, solving the problem of low ion conductivity of existing solid electrolytes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of batteries, and in particular, to a supramolecular ionic liquid, a solid electrolyte membrane, a solid lithium metal battery and a device. Background Art

[0002] Lithium metal has become the best choice for the negative electrode material of the next generation of high energy density secondary batteries due to its advantages such as high theoretical specific capacity, low reduction potential and low density. However, the industrial application of lithium metal negative electrodes still faces challenges. Among them, the irregular deposition of lithium ions on the negative electrode surface causes the uncontrollable growth of lithium dendrites, which causes safety problems during the use of lithium metal batteries, thus restricting the widespread application of lithium metal batteries. All-solid-state lithium metal batteries that use solid electrolytes instead of organic liquid electrolytes are expected to fundamentally solve the safety problems of batteries and improve the energy density of batteries at the same time, so they have become a research hotspot.

[0003] In recent years, research on electrolytes based on polymer materials has made great progress, but their ionic conductivity at room temperature is still very low; and supramolecular materials, as a new type of material bonded by non-covalent bonds, have attracted attention since the end of the last century due to their unique assembly structure and excellent physical and chemical properties, but have not yet been used in the field of solid-state electrolytes. Summary of the invention

[0004] In view of the problems existing in the background technology, the present application provides a supramolecular ionic liquid, a solid electrolyte membrane, a solid lithium metal battery and a device.

[0005] In a first aspect, the present application provides a supramolecular ionic liquid having a triphenylene structure as shown in formula (I):

[0006]

[0007] Among them, R 1 R is selected from an ether group, a polyether group, a halogenated ether group or a halogenated polyether group having 1 to 16 carbon atoms; 2 It is selected from ether groups or polyether groups having 1 to 16 carbon atoms.

[0008] The supramolecular ionic liquid provided in the first aspect of the present application has an ionic conductivity of up to 10 -3 S / cm, and the ionic conductivity of the solid electrolyte membrane prepared by it is also 10 -3 S / cm or above, close to the level of liquid electrolyte, which can solve the problem of low ion conductivity commonly found in existing solid electrolyte materials.

[0009] The ionic conductivity of the supramolecular ionic liquid of the present invention is closely related to the length of its side chain. 1 , R 2When the number of carbon atoms in the 1 , R 2 The chain length is too long, which affects the order of the π-π stacking structure in the supramolecular ionic liquid and also has an adverse effect on the construction of the ion migration channel, resulting in poor ionic conductivity of the supramolecular ionic liquid and the solid electrolyte membrane at 25°C. 1 R is selected from an ether group, a polyether group, a halogenated ether group or a halogenated polyether group having 1 to 16 carbon atoms; 2 It is selected from ether groups or polyether groups having 1 to 16 carbon atoms.

[0010] Optional, R 1 Selected from the structure shown in formula (II):

[0011]

[0012] Wherein, m1 is selected from 1 to 6, n1 is selected from 1 to 5, p1 is selected from 0 to 4, and Y is selected from H, F, Cl or Br.

[0013] Further optionally, formula (II) satisfies at least one of the following conditions: (1) m1 is selected from 2 to 3; (2) n1 is selected from 2 to 3; (3) p1 is selected from 1 to 2; (4) Y is selected from H or F.

[0014] When R 1 The chain length is within a suitable range, the π-π stacking structure in the supramolecular ionic liquid has better order, and the free radical volume is of appropriate size, which is beneficial to the construction of ion migration channels and the enhancement of lithium ion migration ability.

[0015] When R 1 When the terminal is unsubstituted, the supramolecular ionic liquid has good ionic conductivity and is easy to prepare and obtain. 1 After the terminal is substituted by halogen, the supramolecular ionic liquid still has good ionic conductivity; especially in R 1 In the case of terminal F substitution, the LiF generated during the battery cycle helps to form a stable interface, thereby further improving the battery's cycle performance.

[0016] Optional, R 2 Selected from the structure shown in formula (III):

[0017]

[0018] Among them, when n2 is not 0, m2 is selected from 1 to 6, n2 is selected from 1 to 5, and p2 is selected from 0 to 4; when n2 is 0, p2 is selected from 1 to 16, and further optionally, when n2 is 0, p2 is selected from 4 to 10.

[0019] When n2 is not 0, formula (III) satisfies at least one of the following conditions: (1) m2 is selected from 2 to 3; (2) n2 is selected from 2 to 3; (3) p2 is selected from 1 to 2.

[0020] When n2 is not 0, the supramolecular ionic liquid is a fully ether chain substituted structure with better ionic conductivity. However, the fully ether chain substituted supramolecular ionic liquid has a strong fluidity. When the polymer substrate is introduced to further prepare the solid electrolyte membrane, the interaction between the supramolecular ionic liquid and the polymer substrate increases, which is not conducive to the mechanical strength of the solid electrolyte membrane. Therefore, the ether oxygen repeating units in R2 should not be too many. Optionally, m2 is selected from 1 to 6, n2 is selected from 1 to 5, and p2 is selected from 0 to 4. Further optionally, m2 is selected from 2 to 3; n2 is selected from 2 to 3; p2 is selected from 1 to 2.

[0021] When n2 is 0, p2 is selected from 1 to 16; further, when n2 is 0, p2 is selected from 4 to 10. 2 Having a suitable chain length is conducive to the formation of a stable columnar structure through π-π stacking self-assembly of the triphenylene structure, thereby improving the ionic conductivity of the supramolecular ionic liquid and the solid electrolyte membrane.

[0022] Specifically, R in formula (I) 1 , R 2 Can be selected from (I-1) to (I-22):

[0023]

[0024] Optionally, the supramolecular ionic liquid provided in the present application is a columnar structure formed by self-assembly of multiple triphenylene structures through π-π stacking.

[0025] Among them, the q value of the small angle X-ray scattering peak of the supramolecular ionic liquid is 15.5nm -1 ~18.8nm -1 . Optional, q value is 16.0nm -1 ~18.5nm -1 . Optionally, the q value is 16.3nm -1 ~18.2nm -1 When the q value is within the above range, the interdisk spacing between the multiple triphenylene structures in the supramolecular ionic liquid is within a relatively suitable range, inducing the triphenylene structure to stack into a better columnar phase structure via π-π, so that a better ion transmission channel is formed inside the supramolecular ionic liquid structure, thereby improving the ion conductivity.

[0026] Optionally, the ionic conductivity of the supramolecular ionic liquid provided in the present application at 25°C is 2*10 -5 S / cm~7*10 -3S / cm; further optionally, the ionic conductivity of the supramolecular ionic liquid provided in the present application at 25°C is 1.5*10 -3 ~6.5*10 -3 S / cm.

[0027] In a second aspect, the present application provides a solid electrolyte membrane, which comprises the supramolecular ionic liquid of the first aspect of the present application, and the solid electrolyte membrane provided by the second aspect of the present application has an ionic conductivity of 10 -3 S / cm and above, close to the level of liquid electrolyte.

[0028] The solid electrolyte membrane provided in the present application further comprises a polymer matrix, and the polymer matrix meets at least one of the following conditions: (1) the polymer matrix comprises a viscoelastic polymer, and the molecular weight of the polymer matrix is ​​1,000 to 2,000,000; (2) the crystallinity of the polymer matrix is ​​1% to 40%, and optionally, the crystallinity of the polymer matrix is ​​5% to 25%; (3) the polymer matrix comprises a first polymer and a second polymer, the molecular weight of the first polymer is 400,000 to 800,000, and the molecular weight of the second polymer is 1,000 to 10,000. ; Optionally, the mass ratio of the first polymer to the second polymer is 10:1 to 5:1; (4) the polymer matrix is ​​selected from one or more of polyethylene oxide, polyethylene terephthalate, polyimide, polyvinylidene fluoride, polymethyl methacrylate, polyacrylonitrile, polypropylene carbonate, polyvinyl chloride or vinylidene fluoride / 2-acrylamide-2-methylpropane sulfonic acid / trimethylolpropane triacrylate / hyperbranched polyacrylate / methyl methacrylate copolymer; Optionally, the polymer matrix is ​​selected from one or more of polyethylene oxide, polyvinylidene fluoride or polymethyl methacrylate.

[0029] The solid electrolyte membrane provided in the present application further comprises a lithium salt, and the lithium salt is selected from LiPF 6 , LiBF 4 、LiClO 4 、LiAsF 6 、LiCF 3 SO 3 , LiFSI or LiTFSI. Further optionally, the lithium salt is LiTFSI.

[0030] According to the difference in the dissociation ability of the polymer substrate to different lithium salts, when the lithium salt LiTFSI is used, the ionic conductivity of the solid electrolyte membrane and the capacity and cycle performance of the solid-state lithium metal battery are better.

[0031] In a third aspect, the present application provides a method for preparing the solid electrolyte membrane of the second aspect of the present application, comprising the following steps: providing a polymer matrix, a lithium salt, and the supramolecular ionic liquid described in the first aspect of the present application; mixing, hot pressing, and vacuum annealing the above substances to obtain the solid electrolyte membrane.

[0032] Optionally, the mass ratio of polymer matrix, lithium salt and supramolecular ionic liquid is 100:(5-40):(10-80). Optionally, the weighed substances are mixed, placed in a 1-20 MPa environment, and hot pressed at 50-100° C. Optionally, vacuum annealing is performed at 60° C.-80° C. for 1-8 hours.

[0033] In a fourth aspect, the present application provides a solid-state lithium metal battery, comprising the solid-state electrolyte membrane of the second aspect of the present application.

[0034] In a fifth aspect, the present application provides a device, comprising the solid-state lithium metal battery of the fourth aspect of the present application, and the solid-state lithium metal battery can be used as a power source for the device or an energy storage unit for the device.

[0035] Since the supramolecular ionic liquid provided in this application has an ionic conductivity of up to 10 -3 S / cm, and the ionic conductivity of the solid electrolyte membrane prepared by it is also 10 -3 S / cm or above. Therefore, the all-solid-state lithium metal battery prepared by replacing the existing organic liquid electrolyte with the solid electrolyte membrane provided by the present application is expected to fundamentally solve the safety problem of the battery and at the same time improve the battery energy density and cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 is a hydrogen nuclear magnetic resonance spectrum of the product of the supramolecular ionic liquid preparation example 1 of the present application;

[0037] Figure 2 is a SAXS spectrum of the supramolecular ionic liquid preparation example 1 of the present application, wherein curve 1 represents the supramolecular ionic liquid, curve 2 represents the electrolyte membrane after annealing, and curve 3 represents the electrolyte membrane before annealing;

[0038] Figure 3 is a three-dimensional diagram of a solid-state lithium metal battery according to a specific embodiment of the present application;

[0039] Figure 4 yes Figure 3 An exploded view of a solid-state lithium metal battery is shown;

[0040] Figure 5 is a three-dimensional diagram of a battery module according to a specific embodiment of the present application;

[0041] Figure 6is a three-dimensional diagram of a battery pack according to a specific embodiment of the present application;

[0042] Figure 7 yes Figure 6 An exploded view of the battery pack shown;

[0043] Figure 8 is a schematic diagram of a device according to a specific embodiment of the present application;

[0044] The reference numerals are described as follows:

[0045] 1 battery pack;

[0046] 2 upper box;

[0047] 3 lower box;

[0048] 4 battery modules;

[0049] 5Solid-state lithium metal battery;

[0050] 51 housing;

[0051] 52 electrode assembly;

[0052] 53 Top cover assembly. DETAILED DESCRIPTION

[0053] The present application is further described below in conjunction with specific implementations. It should be understood that these specific implementations are only used to illustrate the present application and are not used to limit the scope of the present application.

[0054] Supramolecular ionic liquids

[0055] According to the first aspect of the present application, some embodiments of the present application provide a supramolecular ionic liquid having a triphenylene structure shown in formula (I):

[0056]

[0057] Among them, R 1 R is selected from an ether group, a polyether group, a halogenated ether group or a halogenated polyether group having 1 to 16 carbon atoms; 2 It is selected from ether groups or polyether groups having 1 to 16 carbon atoms.

[0058] The ionic conductivity of the supramolecular ionic liquid provided in this application is as high as 10 -3 S / cm, and the ionic conductivity of the solid electrolyte membrane prepared by it is also 10 -3 S / cm or above, close to the level of liquid electrolyte, which can solve the problem of low ion conductivity commonly found in existing solid electrolyte materials.

[0059] In some embodiments of the present application, R 1Selected from the structure shown in formula (II):

[0060]

[0061] Wherein, m1 is selected from 1 to 6, n1 is selected from 1 to 5, p1 is selected from 0 to 4, and Y is selected from H, F, Cl or Br.

[0062] In some embodiments of the present application, formula (II) satisfies at least one of the following conditions: (1) m1 is selected from 2 to 3; (2) n1 is selected from 2 to 3; (3) p1 is selected from 1 to 2; (4) Y is selected from H or F.

[0063] In some embodiments of the present application, R 2 Selected from the structure shown in formula (III):

[0064]

[0065] In some embodiments of the present application, m2 is selected from 1 to 6, n2 is selected from 1 to 5, and p2 is selected from 0 to 4.

[0066] In some embodiments of the present application, n2 is 0, and p2 is selected from 1 to 16.

[0067] In some embodiments of the present application, n2 is 0, and p2 is selected from 4 to 10.

[0068] In some embodiments of the present application, n2 is not 0, and formula (III) satisfies at least one of the following conditions: (1) m2 is selected from 2 to 3; (2) n2 is selected from 2 to 3; (3) p2 is selected from 1 to 2.

[0069] In some embodiments of the present application, R in formula (I) 1 , R 2 Can be selected from (I-1) to (I-22):

[0070]

[0071] The supramolecular ionic liquid provided in the present application is a columnar structure formed by self-assembly of multiple triphenylene structures through π-π stacking.

[0072] In some embodiments of the present application, the q value of the small angle X-ray scattering peak of the supramolecular ionic liquid provided in the present application is 15.5 nm -1 ~18.8nm -1 .

[0073] In some embodiments of the present application, the q value of the small angle X-ray scattering peak of the supramolecular ionic liquid provided in the present application is 16.0 nm -1 ~18.5nm -1 .

[0074] In some embodiments of the present application, the q value of the small angle X-ray scattering peak of the supramolecular ionic liquid provided in the present application is 16.3 nm -1 ~18.2nm -1 .

[0075] The q value of the small-angle X-ray scattering peak of the supramolecular ionic liquid reflects the disk spacing of triphenylene in π-π stacking. When the q value of the small-angle X-ray scattering peak of the supramolecular ionic liquid of the present application is within the above range, the disk spacing between multiple triphenylene structures in the supramolecular ionic liquid is within a more appropriate range, which can induce triphenylene to form a better columnar phase structure through π-π stacking, so that a better ion transport channel is formed inside the supramolecular ionic liquid structure, thereby improving the ion conductivity.

[0076] In some embodiments of the present application, the ionic conductivity of the supramolecular ionic liquid provided in the present application at 25°C is 2*10 -5 S / cm~7*10 -3 S / cm.

[0077] In some embodiments of the present application, the ionic conductivity of the supramolecular ionic liquid provided in the present application at 25° C. is 1.5*10 -3 ~6.5*10 -3 S / cm.

[0078] Preparation of supramolecular ionic liquids

[0079]

[0080] in,

[0081] R 3 An ether group, a polyether group, a halogenated ether group or a halogenated polyether group having 1 to 16 carbon atoms;

[0082] Furthermore, R 3 It can be selected from the structure shown in formula (III):

[0083]

[0084] The definitions of m1, n1, p1 and Y are the same as in the claims.

[0085] R 4 An ether group or a polyether group having 1 to 16 carbon atoms;

[0086] Furthermore, R 4 It can be selected from the structure shown in formula (IV):

[0087]

[0088] The definitions of n2, m2, n2 and p2 are the same as in the claims.

[0089] Catechol, Br-R 3 , anhydrous potassium carbonate, catalytic amount of KI in a three-necked bottle, add anhydrous ethanol, constant temperature oil bath 100 ° C, mechanical stirring, reflux reaction, the solution is gray at first, and then gradually darkens; react for 48 hours, filter out the gray granular insoluble matter, add dilute hydrochloric acid (10% v / v) to the brown filtrate, and then extract with dichloromethane (2×100mL), remove dichloromethane by rotary evaporation to obtain a brown liquid; finally column purification (petroleum ether: dichloromethane = 2:1 [v / v]).

[0090] The product of the previous step was placed in a three-necked flask, and an appropriate amount of dry dichloromethane was added. The mixture was mechanically stirred and ice-salt bathed. Anhydrous ferric chloride was added in batches under nitrogen protection. After stirring for 30 minutes, the ice-salt bath was removed and the reaction was allowed to react at room temperature. TLC (petroleum ether: dichloromethane = 1:1, v / v) was used to track the reaction process. After the reaction was completed, 80 mL of methanol was slowly added dropwise under ice-salt bath. After stirring for 1 hour, distilled water was added. The mixture was extracted with dichloromethane, and dichloromethane was evaporated to obtain a black solid. The crude product was passed through a column (petroleum ether: dichloromethane = 1:1, v / v), and the eluted components were concentrated and passed through a column again (petroleum ether: ethyl acetate = 30:1, v / v). The yellow solution obtained was concentrated to obtain a light yellow solid product R. 3 -TP-OH was dried in a vacuum oven at room temperature overnight to obtain a light yellow solid.

[0091] Williamson reaction: R 3 -TP-OH and Br-R 4 -S0 3 H was dissolved in DMF, 10.0 g LiOH was added, the mixture was heated to 70° C., stirred and refluxed overnight, the product was precipitated with ethanol, washed with water three times, and vacuum dried to obtain a light yellow viscous liquid, which was the supramolecular ionic liquid of the present invention.

[0092] Examples of the preparation of supramolecular ionic liquids

[0093] Preparation Example 1

[0094] 10.98g catechol, 24.02g Br-R 3 41g of anhydrous potassium carbonate and a catalytic amount of KI were placed in a 250mL three-necked bottle, and 150mL of anhydrous ethanol was added. The mixture was placed in a constant temperature oil bath at 100°C, mechanically stirred, and refluxed. The solution was gray at first and then gradually darkened. The reaction was continued for 48h. After the gray granular insoluble matter was removed by suction filtration, 200mL of dilute hydrochloric acid (10% v / v) was added to the brown filtrate. The mixture was extracted with dichloromethane (2×100mL). The dichloromethane was removed by rotary evaporation to obtain a brown liquid. The mixture was purified by column (petroleum ether: dichloromethane = 2:1 [v / v]). The yield was 21.05g, 90.8%.

[0095] 21.05g of the product from the previous step was placed in a 250mL three-necked flask, and 115mL of dry dichloromethane was added. The mixture was stirred mechanically, and then an ice-salt bath was added. Under nitrogen protection, 39g of anhydrous ferric chloride was added in batches. After stirring for 30min, the ice-salt bath was removed. The reaction was allowed to react at room temperature. TLC (petroleum ether: dichloromethane = 1:1, v / v) was used to track the reaction process. After the reaction was completed, 80mL of methanol was slowly added dropwise under an ice-salt bath. After stirring for 1h, 385mL of distilled water was added. The mixture was extracted with 1000mL of dichloromethane, and the dichloromethane was evaporated to obtain a black solid. The crude product was passed through a column (petroleum ether: dichloromethane = 1:1, v / v), and the eluted components were concentrated and passed through a column again (petroleum ether: ethyl acetate = 30:1, v / v). The yellow solution obtained was concentrated to obtain a light yellow solid product R. 3 -TP-OH, after drying in a vacuum oven at room temperature overnight, 4.74 g of light yellow solid was obtained, with a yield of 21%.

[0096] Using Williamson reaction, 3.0 g R 3 -TP-OH and 6.0 g Br-R 4 -SO 3 H Dissolve in DMF, add 10.0 g LiOH, heat to 70 °C, stir and reflux overnight, precipitate the product with ethanol, wash with water 3 times, and vacuum dry to obtain a light yellow viscous liquid R 3 -TP-R 4 -SO 3 Li (supramolecular ionic liquid of Example 4). Yield: 17%.

[0097] Product characterization:

[0098] H NMR ( 1 H NMR) and carbon spectroscopy ( 13 C): Bruker ARX 400 (400 MHz) and ARX 500 (500 MHz) nuclear magnetic resonance spectrometers.

[0099] Small / wide angle X-ray scattering (SAXS / WAXS): Anton Paar SAXSess mc 2 The high-throughput small-angle X-ray scattering instrument is equipped with an Anton Paar TCS120 hot stage. It uses a Cu target as the X-ray source. The wavelength λ of the monochromated CuKα ray is 0.1542nm. It can simultaneously perform small-angle SAXS and wide-angle WAXS measurements, and the collection q value range is 0.06 to 29nm. -1 , where q = 4πsinθ / λ, 2θ is the scattering angle. The solid powder sample was tested by wrapping it in aluminum foil, and then the background signal of the aluminum foil was subtracted using SAXSquant software 3.80.

[0100] Preparation Example 2

[0101] The same method as Preparation Example 1 was used. A yellow viscous liquid (the supramolecular ionic liquid of Example 9) was obtained with a yield of 22%.

[0102] Preparation Example 3

[0103] The same method as Preparation Example 1 was used. A light yellow viscous liquid (the supramolecular ionic liquid of Example 19) was obtained with a yield of 20%.

[0104] Preparation Example 4

[0105] The same method as Preparation Example 1 was used. A light yellow liquid (the supramolecular ionic liquid of Example 22) was obtained with a yield of 16%.

[0106] Preparation Example 5

[0107] The same method as in Preparation Example 1 was used to prepare R 3 =*-CH 2 -O-CH 3 , A dark yellow powder (the supramolecular ionic liquid of Example 1) was obtained with a yield of 12%.

[0108] Solid electrolyte membrane

[0109] According to the second aspect of the present application, some embodiments of the present application provide a solid electrolyte membrane, which comprises the supramolecular ionic liquid according to the first aspect of the present application.

[0110] In some embodiments of the present application, the solid electrolyte membrane provided in the present application further comprises a polymer matrix, and the polymer matrix meets at least one of the following conditions: (1) the polymer matrix comprises a viscoelastic polymer, and the molecular weight of the polymer matrix is ​​1,000 to 2,000,000; (2) the crystallinity of the polymer matrix is ​​1% to 40%, and can be 5% to 25%; (3) the polymer matrix comprises a first polymer and a second polymer, and the molecular weight of the first polymer is 400,000 to 800,000, and the molecular weight of the second polymer is 1,000 to 10,000. 0; Optionally, the mass ratio of the first polymer to the second polymer is 10:1 to 5:1; (4) the polymer matrix is ​​selected from one or more of polyethylene oxide, polyethylene terephthalate, polyimide, polyvinylidene fluoride, polymethyl methacrylate, polyacrylonitrile, polypropylene carbonate, polyvinyl chloride or vinylidene fluoride / 2-acrylamide-2-methylpropane sulfonic acid / trimethylolpropane triacrylate / hyperbranched polyacrylate / methyl methacrylate copolymer; Further optionally, the polymer matrix is ​​selected from one or more of polyethylene oxide, polyvinylidene fluoride or polymethyl methacrylate.

[0111] The solid electrolyte membrane provided in the present application further comprises a lithium salt, and the lithium salt is selected from LiPF 6 , LiBF 4 、LiClO 4 、LiAsF 6 、LiCF 3 SO 3 , LiFSI or LiTFSI or more; further optionally, the lithium salt is selected from LiTFSI.

[0112] Preparation of solid electrolyte membrane

[0113] According to the third aspect of the present application, some embodiments of the present application provide a method for preparing a solid electrolyte membrane, comprising the following steps: providing a polymer matrix, a lithium salt, and the supramolecular ionic liquid described in the first aspect of the present application; mixing, hot pressing, and vacuum annealing the above substances to obtain the solid electrolyte membrane.

[0114] Optionally, the mass ratio of polymer matrix, lithium salt and supramolecular ionic liquid is 100:(5-40):(10-80). Optionally, the weighed substances are mixed, placed in a 1-20 MPa environment, and hot pressed at 50-100° C. Optionally, vacuum annealing is performed at 60° C.-80° C. for 1-8 hours.

[0115] Solid-state lithium metal battery

[0116] According to a fourth aspect of the present application, some embodiments of the present application provide a solid-state lithium metal battery, which includes the solid-state electrolyte membrane of the second aspect of the present application.

[0117] Specifically, the solid-state lithium metal battery provided in some embodiments of the present application includes: a positive electrode plate, a negative electrode plate, and a solid electrolyte membrane spaced between the positive electrode plate and the negative electrode plate, wherein the solid electrolyte membrane is the solid electrolyte membrane of the second aspect of the present application.

[0118] Except for using the solid electrolyte membrane of the second aspect of the present application, the structure and preparation method of the solid-state lithium metal battery of the present application are known per se.

[0119] In a solid-state lithium metal battery, a positive electrode plate includes a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector. In the positive electrode plate, the positive electrode active material layer can be disposed on one surface of the positive electrode current collector or on both surfaces of the positive electrode current collector.

[0120] Those skilled in the art may select a suitable method to prepare the positive electrode sheet, for example, the method may include the following steps: mixing the positive electrode active material, the binder, and the conductive agent to form a slurry, and then coating the slurry on the positive electrode current collector.

[0121] Among them, there is no particular restriction on the specific type of positive electrode active material, as long as it can meet the requirements of embedding and extracting lithium ions. The positive electrode active material can be a layered structure material that allows lithium ions to diffuse in a two-dimensional space, or a spinel structure that allows lithium ions to diffuse in a three-dimensional space. Optionally, the positive electrode active material can be selected from one or more of lithium transition metal oxides, lithium transition metal oxides, and compounds obtained by adding other transition metals or non-transition metals or non-metals. Specifically, the positive electrode active material can be selected from one or more of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and lithium phosphates with an olivine structure.

[0122] Among them, the general formula of the lithium-containing phosphate with olivine structure can be LiFe 1-x-y Mn x M' y PO 4 , 0≤x≤1, 0≤y<1, 0≤x+y≤1, M' is selected from one or more of other transition metal elements or non-transition metal elements except Fe and Mn, and M' can be selected from one or more of Cr, Mg, Ti, Al, Zn, W, Nb, and Zr. Optionally, the lithium-containing phosphate with olivine structure is selected from one or more of lithium iron phosphate, lithium manganese phosphate, and lithium manganese iron phosphate.

[0123] Lithium transition metal oxide selected from LiCoO 2 、LiMnO 2 、LiNiO 2 、LiMn 2 O4 、LiNi x Co y Mn 1-x-y O 2 、LiNi x Co y Al 1-x-y O 2 、LiNi x Mn 2-x O 4 One or more of the following, wherein 0<x<1, 0<y<1, 0<x+y<1. Optionally, the lithium transition metal oxide is selected from LiCoO 2 、LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 、LiNi 0.5 Co 0.2 Mn 0.3 O 2 、LiNi 0.6 Co 0.2 Mn 0.2 O 2 、LiNi 0.8 Co 0.1 Mn 0.1 O 2 、LiNi 0.8 Co 0.15 Mn 0.05 O 2 、LiNi 0.8 Co 0.15 Al 0.05 O 2 、LiNi 0.5 Mn 1.5 O 4 、LiMn 2 O 4 One or more of the .

[0124] In the positive electrode sheet, the positive electrode active material layer may also include a conductive agent and a binder, wherein the type and content of the conductive agent and the binder are not specifically limited and can be selected according to actual needs. The binder generally includes a fluorinated polyolefin binder. Relative to the fluorinated polyolefin binder, water is generally a good solvent, that is, the fluorinated polyolefin binder generally has good solubility in water. For example, the fluorinated polyolefin binder may include but is not limited to polyvinylidene fluoride (PVDF), vinylidene fluoride copolymers or their modified (for example, carboxylic acid, acrylic acid, acrylonitrile, etc.) derivatives. In the positive electrode material layer, since the conductivity of the binder itself is poor, the amount of the binder cannot be too high. Optionally, the mass percentage of the binder in the positive electrode active material layer is less than or equal to 2wt% to obtain a lower electrode sheet impedance. The conductive agent of the positive electrode sheet may be a variety of conductive agents suitable for lithium ion (secondary) batteries in the art, for example, may be a combination of one or more including but not limited to acetylene black, conductive carbon black, carbon fiber (VGCF), carbon nanotubes (CNT), Ketjen black, etc. The weight of the conductive agent may account for 1 wt% to 10 wt% of the total weight of the positive electrode material layer. Optionally, the weight ratio of the conductive agent to the positive electrode active material in the positive electrode sheet is greater than or equal to 1.5:95.5.

[0125] In the positive electrode sheet, the type of positive electrode current collector is not specifically limited and can be selected according to actual needs. The positive electrode current collector can usually be a layer body, and the positive electrode current collector is usually a structure or part that can collect current. The positive electrode current collector can be various materials in the art that are suitable for use as a positive electrode current collector for an electrochemical energy storage device. For example, the positive electrode current collector can include but is not limited to metal foil, and more specifically can include but is not limited to nickel foil and aluminum foil.

[0126] In a solid-state lithium metal battery, the negative electrode plate may include a negative electrode current collector and a lithium metal layer located on the surface of the negative electrode current collector. The negative electrode current collector is usually a structure or part for collecting current. The negative electrode current collector may be any material suitable for use as a negative electrode current collector for an electrochemical energy storage device in the art. For example, the negative electrode current collector may include but is not limited to metal foil, and more specifically may include but is not limited to copper foil. In addition, the negative electrode plate may also be a lithium plate.

[0127] The present application has no particular limitation on the shape of the solid-state lithium metal battery, which may be square or any other shape. Figure 3 shows a three-dimensional view of a solid-state lithium metal battery according to a specific embodiment of the present invention, Figure 4 yes Figure 3 An exploded view of a solid-state lithium metal battery is shown. Figure 3 and Figure 4According to the present application, the solid-state lithium metal battery 5 (hereinafter referred to as the battery cell 5) includes an outer package 51, an electrode assembly 52, and a top cover assembly 53. The electrode assembly 52 is accommodated in the shell 51, and the number of the electrode assembly 52 is not limited, and can be one or more.

[0128] It should be noted that Figure 3 The battery cell 5 shown is a can-type battery, but the present application is not limited thereto. The battery cell 5 may be a pouch-type battery, that is, the housing 51 is replaced by a metal plastic film and the top cover assembly 53 is eliminated.

[0129] In some embodiments of the present application, solid-state lithium metal batteries can be assembled into a battery module. The battery module can contain multiple solid-state lithium metal batteries, and the specific number can be adjusted according to the application and capacity of the battery module. Figure 5 4 is a perspective view of a battery module 4 as an example. Figure 5 In the battery module 4, the plurality of solid-state lithium metal batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. The plurality of solid-state lithium metal batteries 5 may further be fixed by fasteners. Optionally, the battery module 4 may further include a housing having a housing space, and the plurality of solid-state lithium metal batteries 5 are accommodated in the housing space.

[0130] In some embodiments of the present application, the battery modules mentioned above may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack. Figure 6 is a stereoscopic view of a battery pack 1 as an example, Figure 7 yes Figure 6 Exploded view of the battery pack shown. Figure 6 and Figure 7 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.

[0131] Device

[0132] The fifth aspect of the present application provides a device, which includes the solid-state lithium metal battery of the fourth aspect of the present application, and the solid-state lithium metal battery is used as a power source of the device or an energy storage unit of the device. The device can be, but is not limited to, a mobile device (such as a mobile phone, a laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship and a satellite, an energy storage system, etc.

[0133] The device can select solid-state lithium metal batteries, battery modules or battery packs according to its usage requirements.

[0134] Figure 8 A schematic diagram of a device according to a specific embodiment of the present application is shown. The device may be a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. In order to meet the device's requirements for high power and high energy density of a solid-state lithium metal battery (i.e., the secondary battery of the present application), a battery pack or a battery module may be used.

[0135] As another example, the device may be a mobile phone, a tablet computer, a laptop computer, etc. The device is usually required to be light and thin, and a solid-state lithium metal battery (ie, the secondary battery of the present application) may be used as a power source.

[0136] The advantages of the present application are further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present application and are not used to limit the scope of the present application. Unless otherwise specified, the various parameters involved in this specification have general meanings known in the art and can be measured by methods known in the art. For example, the method provided in the examples of the present application can be tested. In addition, the scope and options of the various different parameters provided in the various embodiments can be combined arbitrarily, and the various combinations obtained are all considered to be within the scope of the disclosure of the present application.

[0137] Examples 1 to 25

[0138] Preparation of solid electrolyte membrane

[0139] 100 parts of polymer matrix, 30 parts of lithium salt and 40 parts of supramolecular ionic liquid were weighed by mass. The above-mentioned substances were mixed, placed in a 10MPa environment, and hot pressed at 70°C. Vacuum annealing was performed at 60°C to 80°C for 4 hours to obtain a solid electrolyte membrane.

[0140] The positive electrode sheet and the negative electrode sheet are prepared according to conventional methods in the art.

[0141] Positive electrode: LiNi 0.8 Co 0.1 Mn 0.1 O 2 Conductive agent, conductive carbon, and binder polyvinylidene fluoride (PVDF) are mixed evenly in a mass ratio of 96:2:2 to form a lithium-ion battery positive electrode slurry with a certain viscosity. The positive electrode slurry is coated on the current collector aluminum foil, dried at 85°C and then cold pressed, and then trimmed, cut into pieces, and divided into strips. After dividing into strips, it is dried at 85°C under vacuum conditions for 4 hours, and the pole ears are welded to make lithium battery positive electrode sheets.

[0142] Negative electrode sheet: The negative electrode sheet is prepared by calendering. In an environment with humidity ≤ 0.2% and temperature 23°C, a 100μm lithium ribbon is attached to one side of a 6μm copper current collector, and the roller temperature is 25°C. The single-sided negative electrode sheet is prepared by continuous rolling; after winding, the coil temperature drops to 20°C, and the double-sided negative electrode sheet is prepared by the same method.

[0143] Preparation of solid-state lithium metal batteries

[0144] The centers of the positive electrode sheet, solid electrolyte membrane, and negative electrode sheet are aligned and stacked in sequence, and cold pressed at room temperature and 250 MPa for 2 minutes to obtain a battery cell unit. After cold pressing, 10 layers of battery cell units are placed in an outer package for encapsulation to obtain a solid-state lithium metal battery.

[0145] Comparative Examples 1 to 8

[0146] The preparation steps of Comparative Examples 1 to 8 are basically the same as those of Examples 1 to 25, except that: in Comparative Examples 1 to 7, different R 1 , R 2 The solid electrolyte membrane is prepared by using supramolecular ionic liquid, and the electrolyte membrane is prepared by using PEO / LiTFSI polymer solid electrolyte in Comparative Example 8.

[0147] The specific parameters of the supramolecular ionic liquids and solid electrolyte membranes in Examples 1 to 25 are shown in Table 1; the specific parameters of the supramolecular ionic liquids and solid electrolyte membranes in Comparative Examples 1 to 8 are shown in Table 2.

[0148] Table 1

[0149]

[0150] Table 2

[0151]

[0152] Cycle performance test:

[0153] The specific test method is: at 25°C, constant current charging and constant current discharging are used, the charging and discharging voltage range is 2.8~4.3V, the charging and discharging rate is 0.5C, and the initial capacity of the battery is recorded as C 0 , the battery completes a full charge and discharge, which is recorded as a cycle; charge and discharge according to the above method, and test the battery capacity after each cycle until the battery capacity is 80%*C 0 , record the number of cycles at this time.

[0154] The battery cycle performance test results of Examples 1 to 25 are shown in Table 3; the battery cycle performance test results of Comparative Examples 1 to 8 are shown in Table 4.

[0155] Table 3

[0156]

[0157] Table 4

[0158]

[0159] Test result analysis:

[0160] Examples 1 to 25, Comparative Examples 1 to 8

[0161] In Comparative Example 8, the existing PEO / LiTFSI polymer solid electrolyte is used, and its ionic conductivity at 25°C is only 8.7*10 -6 S / cm. In contrast, the ionic conductivity of the supramolecular ionic liquids of Examples 1 to 25 at 25°C is as high as 10 - 3 S / cm, and the ionic conductivity of its super-prepared solid electrolyte membrane is also 10 -3 S / cm or above, which is close to the level of liquid electrolyte, indicating that the supramolecular ionic liquid and solid electrolyte membrane provided by the present application can effectively solve the problem of low ion conductivity of existing solid electrolytes.

[0162] Comparative Examples 5 to 7 show several supramolecular ionic liquids and solid electrolyte membranes with similar structures. It can be seen that their ionic conductivity at 25° C. is still very low, indicating that the side chain structure of the supramolecular ionic liquid provided in the present application is closely related to its ionic conductivity.

[0163] Comparative Examples 1 to 4 have similar supramolecular ionic liquid core structures as those of Examples 1 to 25. However, in Examples 1 to 25, R 1 , R 2 The number of carbon atoms in is less than 16; while in Comparative Examples 1 to 4, R 1 , R 2 The number of carbon atoms in the R is more than 16. In this case, the ionic conductivity of the supramolecular ionic liquid and solid electrolyte membrane in Examples 1 to 25 at 25°C is significantly better than that of Comparative Examples 1 to 4. This is because when R 1 , R 2 When the number of carbon atoms in the 1 , R 2 Too long a chain length affects the orderliness of the π-π stacking structure in the supramolecular ionic liquid and also has an adverse effect on the construction of ion migration channels, resulting in poor ionic conductivity of the supramolecular ionic liquid and solid electrolyte membrane at 25°C.

[0164] Examples 1 to 7

[0165] Examples 1 to 7 show that R 2 When R 1The effect of increasing the number of carbon atoms on the ionic conductivity of supramolecular ionic liquids and solid electrolyte membranes. From the data in Tables 1 and 2, we can see that R 2 When R 1 As the number of carbon atoms increases, the ionic conductivity of the supramolecular ionic liquid and the solid electrolyte membrane first increases and then decreases. When m1 is selected from 1 to 6, or selected from 2 to 3; n1 is selected from 1 to 5, or selected from 2 to 3; p1 is selected from 0 to 4, or selected from 1 to 2, R 1 The chain length is within a suitable range, the π-π stacking structure in the supramolecular ionic liquid has better order, and the free radical volume is of appropriate size, which is beneficial to the construction of ion migration channels and the enhancement of lithium ion migration ability, and the ionic conductivity of the supramolecular ionic liquid and the solid electrolyte membrane is increased.

[0166] It is worthwhile to explain that in Example 7, when R 1 When the structure contains terminal hydroxyl groups, the ionic conductivity of the supramolecular electrolyte is still low. However, due to the side reaction between the terminal hydroxyl groups and lithium metal, low ion conductivity lithium oxide is generated, which increases the interface polarization. Therefore, when the supramolecular ionic liquid of Example 7 is used to prepare a solid electrolyte membrane, the ionic conductivity of the solid electrolyte membrane is poor.

[0167] Embodiment 4, Embodiment 8-10

[0168] Examples 4 and 8 to 10 show that R 1 The influence of terminal halogen substitution on the technical effect of the present application. From the data in Table 1 and Table 2, it can be seen that R 1 The terminal halogen substitution has little effect on the ionic conductivity of supramolecular ionic liquids and solid electrolyte membranes, and supramolecular ionic liquids have good ionic conductivity. 1 In the case of terminal F substitution, the LiF generated during the battery cycle helps to form a stable interface, thereby further improving the battery's cycle performance.

[0169] Embodiment 4, Embodiment 11~15

[0170] Examples 4 and 11 to 15 show that R 1 unchanged, R 2 When n2 is 0, R 2 The effect of increasing the number of carbon atoms on the ionic conductivity of supramolecular ionic liquids and solid electrolyte membranes. When p2 is selected from 1 to 16, or from 4 to 10, R 2 Having a suitable chain length is conducive to the formation of a stable columnar structure through π-π stacking self-assembly of the triphenylene structure, thereby improving the ionic conductivity of the supramolecular ionic liquid and the solid electrolyte membrane.

[0171] In addition, when R 2 and R 1When the number of carbon atoms is similar or equal, the columnar structure formed by the π-π stacking self-assembly of the triphenylene structure is the most stable, and the stable columnar structure is conducive to the formation of ion transport channels, so the ionic conductivity of the supramolecular ionic liquid and solid electrolyte membrane is also better.

[0172] Embodiment 4, Embodiment 16~22

[0173] Examples 4 and 16 to 22 show that R 1 unchanged, R 2 When n2 is not 0, R 2 The effect of increasing the number of carbon atoms. 2 When n2 is not 0, the supramolecular ionic liquid is a fully ether chain-substituted structure, and the supramolecular ionic liquid has better ionic conductivity. However, the supramolecular ionic liquid with fully ether chain substitution also has strong fluidity. When the polymer substrate is introduced to further prepare the solid electrolyte membrane, the supramolecular ionic liquid has a strong interaction with the polymer substrate, the mechanical strength of the solid electrolyte membrane is not high, and the ability to inhibit the growth of lithium dendrites is reduced. The battery may have a short circuit risk. Therefore, R 2 The ether oxygen repeating units should not be too many.

[0174] Embodiment 4, Embodiment 23-25

[0175] Examples 4 and 23 to 25 show the technical effect of using the same supramolecular ionic liquid and different lithium salts to prepare a solid electrolyte membrane. According to the difference in the dissociation ability of the polymer substrate to different lithium salts, when the lithium salt LiTFSI is used, the ionic conductivity of the solid electrolyte membrane and the capacity and cycle performance of the solid-state lithium metal battery are better.

[0176] According to the disclosure and teaching of the above description, those skilled in the art may also make changes and modifications to the above implementation. Therefore, the present application is not limited to the specific implementation disclosed and described above, and some modifications and changes to the present application should also fall within the scope of protection of the claims of the present application. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present application.

Claims

1. A supramolecular ionic liquid having a triphenylene structure as shown in formula (I): in, R1 is selected from the structure shown in formula (II): in, m1 is selected from 1 to 6, n1 is selected from 1 to 5, p1 is selected from 0 to 4, Y is selected from H, F, Cl or Br; R2 is selected from the structure shown in formula (III): in, When n2 is not 0, m2 is selected from 1 to 6, n2 is selected from 1 to 5, and p2 is selected from 0 to 4; When n2 is 0, p2 is selected from 1 to 16.

2. The supramolecular ionic liquid according to claim 1, wherein The formula (II) satisfies at least one of the following conditions: (1) m1 is selected from 2 to 3; (2) n1 is selected from 2 to 3; (3) p1 is selected from 1 to 2; (4) Y is selected from H or F.

3. The supramolecular ionic liquid according to claim 1, wherein When n2 is 0, p2 is selected from 4 to 10.

4. The supramolecular ionic liquid according to claim 1, wherein When n2 is not 0, the formula (III) satisfies at least one of the following conditions: (1) m2 is selected from 2 to 3; (2) n2 is selected from 2 to 3; (3) p2 is selected from 1 to 2.

5. The supramolecular ionic liquid according to any one of claims 1 to 4, wherein R1 and R2 in the formula (I) are selected from one of (I-1) to (I-22):

6. The supramolecular ionic liquid according to claim 1, wherein The supramolecular ionic liquid is a columnar structure formed by self-assembly of a plurality of triphenylene structures through π-π stacking.

7. The supramolecular ionic liquid according to claim 1, wherein The q value of the small angle X-ray scattering peak of the supramolecular ionic liquid is 15.5 nm -1 ~18.8nm -1 .

8. The supramolecular ionic liquid according to claim 7, wherein The q value is 16.0 nm -1 ~18.5nm -1 .

9. The supramolecular ionic liquid according to claim 7, wherein The q value is 16.3 nm -1 ~18.2nm -1 .

10. The supramolecular ionic liquid according to any one of claims 1 to 4, wherein The ionic conductivity of the supramolecular ionic liquid at 25°C is 2*10 -5 S / cm~7*10 -3 S / cm.

11. The supramolecular ionic liquid according to claim 10, wherein The ionic conductivity is 1.5*10 -3 ~6.5*10 -3 S / cm.

12. A solid electrolyte membrane, wherein: The method comprises the supramolecular ionic liquid according to any one of claims 1 to 11.

13. The solid electrolyte membrane according to claim 12, wherein: The solid electrolyte membrane further comprises a polymer matrix, and the polymer matrix meets at least one of the following conditions: (1) The polymer matrix comprises a viscoelastic polymer, and the molecular weight of the polymer matrix is ​​1,000 to 2,000,000; (2) The crystallinity of the polymer matrix is ​​1% to 40%; (3) The polymer matrix includes a first polymer and a second polymer, the molecular weight of the first polymer is 400,000 to 800,000, and the molecular weight of the second polymer is 1,000 to 10,000; (4) The polymer matrix is ​​selected from one or more of polyethylene oxide, polyethylene terephthalate, polyimide, polyvinylidene fluoride, polymethyl methacrylate, polyacrylonitrile, polypropylene carbonate, polyvinyl chloride or vinylidene fluoride / 2-acrylamide-2-methylpropane sulfonic acid / trimethylolpropane triacrylate / hyperbranched polyacrylate / methyl methacrylate copolymer.

14. The solid electrolyte membrane according to claim 12 or 13, wherein: The solid electrolyte membrane further comprises a lithium salt, and the lithium salt is selected from one or more of LiPF6, LiBF4, LiClO4, LiAsF6, LiCF3SO3, LiFSI or LiTFSI.

15. A method for preparing a solid electrolyte membrane, wherein the solid electrolyte membrane is the solid electrolyte membrane according to any one of claims 12 to 14, wherein: The following steps are included: Providing a polymer matrix, a lithium salt, and a supramolecular ionic liquid according to any one of claims 1 to 11; The solid electrolyte membrane is prepared by mixing, hot pressing, and vacuum annealing the above-mentioned materials.

16. The method for preparing a solid electrolyte membrane according to claim 15, wherein: The mass ratio of the polymer matrix, the lithium salt, and the supramolecular ionic liquid is 100:(5-40):(10-80).

17. A solid-state lithium metal battery, wherein: Comprising the solid electrolyte membrane according to any one of claims 12 to 14.

18. A device, wherein: Comprising the solid-state lithium metal battery according to claim 17, the solid-state lithium metal battery can be used as a power source for the device or an energy storage unit for the device.

Citation Information

Patent Citations

  • New triphenylene derivative compound

    JP2004115477A